First time fruit growing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Fruit growing in the tropics Agrodok series No.5 52pp ISBN 90 72746 42 2 Published by Agromisa Available from CTA